Development of Contextual-Based Student Worksheets (LKPD) To Improve Reading Skills of Grade II Students at MIN Bah Kapul Pematang Siantar - Egi Syahirah; Andina Halimsyah Rambe (LEMBAGA PENELITIAN DAN PENDIDIKAN (LPP) ARROSYIDIN, 2026)
The low reading ability of lower-grade students remains a fundamental problem in elementary school learning, including among second-grade students at MIN Bah Kapul Pematang Siantar. This condition is influenced by the limited availability of instructional materials that are less engaging and not yet connected to students’ daily life contexts. Therefore, this study aims to develop Contextual-Based Student Worksheets (LKPD) to improve the reading skills of second-grade students at MIN Bah Kapul Pematang Siantar. This research employs a Research and Development (R&D) approach using the ADDIE model, which comprises the stages of analysis, design, development, implementation, and evaluation. The trial subjects in this study were 26 second-grade students. Data collection techniques included observation, questionnaires, and reading ability tests. The results of the study indicate that the developed LKPD is valid, practical, and effective. The validity results show a score of 81% from media experts (very valid) and 80% from material experts (valid). The practicality results indicate positive responses from teachers (98%) and students (81%) with very feasible criteria. Meanwhile, the effectiveness results show an improvement in students’ reading ability, as indicated by the increase in the average pretest score from 56.67 to 84.37 in the posttest, with an N-Gain score of 0.64 (moderate category). Thus, the context-based LKPD developed is suitable for use and effective in improving students’ reading skills.